Novel TGM1 Gene Mutation in a Japanese Patient with Bathing Suit Ichthyosis - Naomi Tani; Nanako Yamada; Tetsuya Okazaki; Takashi Horie; Hajime Nakano; Daisuke Sawamura; Osamu Yamamoto (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)